The effect of using cartooning strategy in learning the motor skills in fencing for cubs aged (8-9) years - Namoos AL-Taie, Dhafer; Nadeem Ahmed, Maysaa (International Journal of Psychosocial Rehabilitation, 2020)
In order to reveal the effect of the cartoon strategy on learning the motor skills in fencing, the researchers applied it to a sample of Diyala School’s (32) cubs, who were divided into the experimental and control groups equally, and after completing the field research procedures of determining the motor skills and the method of their evaluation and preparing the educational units for the strategy and the implementation of tribal posteriori tests, c m p data was processed statistically. The two researchers reached through the results to the most important conclusions: The cartoon strategy has a positive effect on learning the motor skills in dueling. And the presence of significant differences between the experimental and control groups in the post-test and in favor of the experimental group that used the cartoon strategy. The researchers recommend Including the following: The necessity of using teaching methods, methodsand strategies, including the cartoon strategy, which increased the desire and motivation of the youngsters to accept and learn the skills in question, Conducting comparative research and studies between this strategy and other Al-Nadir strategies and knowing the effectiveness of each of them on different samples, whether they are students or players.